(untitled) (Almanack, 2022)
This article is concerned with Fernand Braudel’s conception of the plural temporality and, above all, the longue durée as a practical tool for historical inquiry. Through an examination of the work of Braudel’s colleague Ernst Labrousse, it emphasizes the theoretical and methodological assumptions underlying the practice of serial history as the means to reconstruct such “structural temporalities.” Finally, it treats the concern for the episodic and short-term that characterizes Italian microhistória as a reaction to the dominance of French serial history which, nonetheless remains in relation to Braudel’s conception of plural time. In this way the article seeks to make explicit the relationship between the socalled “second Annales” of Braudel and Italian microhistory and to suggest ways the conceptions of temporality might promote dialogue between diverse historiographical approaches.